Perancangan Alat Pengukur Massa Pada Automatic Machine Measuring Of Mass And Dimension Dengan Metode Dfma - Aulia Rahman; Dodi Sofyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Design of automatic machine measuring of mass and dimension is the initial activity of a series of product manufacturing processes. Design is an important part of producing a complete manufacturing product. The manufacturing process of this machine refers to the Design for Manufacture and Assembly (DFMA) method. DFMA method is a method that provides efficient steps in the manufacturing process. Design for Manufacture (DFM) is one of the manufacturing planning systems that will analyze designs that will be used from several planned design alternatives, until the third design alternative is chosen as the final design for manufacturing. Design for Assembly (DFA) is one of the assembly planning systems that will analyze the design of components and products as a whole. The DFA analysis will produce assembly efficiency values. The value of assembly efficiency from the prototype design in theory is 5.45% with assembly time of 715.05 seconds and the value of assembly efficiency from the prototype in practice is 5.76% with assembly time of 676.54 seconds. Keyword : design, automatic measuring machine, DFM